Cambridge primary English workbook 4 - Burt, Sally (United kingdom : Cambridge university press, 2021)
Cambridge Primary English Workbook 4 is designed to complement the learner's book and help students reinforce and practice the English skills they have learned. It includes a variety of exercises that focus on grammar, vocabulary, reading comprehension, and writing. The workbook encourages students to apply their knowledge in different contexts, with tasks that range from sentence construction to creative writing. The activities are designed to be engaging and challenging, helping students build a deeper understanding of the English language while improving their ability to use it confidently.
Keywords: English : Workbook